Decline in in-patient treatments of genital warts among young Australians following the national HPV vaccination program - Ali, Hammad (BioMed Central, 2013)
BACKGROUND: There has been a rapid decline in the number of young heterosexuals diagnosed with genital warts at outpatient sexual health services since the national human papillomavirus (HPV) vaccination program started in Australia in 2007. We assessed the impact of the vaccination program on the number of in-patient treatments for genital warts. METHODS: Data on in-patient treatments of genital warts in all private hospitals were extracted from the Medicare website. Medicare is the universal health insurance scheme of Australia. In the vaccine period (2007–2011) and pre-vaccine period (2000–2007) we calculated the percentage change in treatment numbers and trends in annual treatment rates in private hospitals. Australian population data were used to calculate rates. Summary rate ratios of average annual trends were determined. RESULTS: Between 2000 and 2011, 6,014 women and 936 men aged 15–44 years underwent in-patient treatment for genital warts in private hospitals. In 15–24 year old women, there was a significant decreasing trend in annual treatment rates of vulval/vaginal warts in the vaccine period (overall decrease of 85.3% in treatment numbers from 2007 to 2011) compared to no significant trend in the pre-vaccine period (summary rate ratio (SRR) = 0.33, p < 0.001). In 25–34 year old women, declining trends were seen in both vaccine and pre-vaccine periods (overall decrease of 33% vs. 24.3%), but the rate of change was greater in the vaccine period (SRR = 0.60, p < 0.001). In 35–44 year old women, there was no significant change in both periods (SRR = 0.91, p = 0.14). In 15–24 year old men, there was a significant decreasing trend in annual treatment rates of penile warts in the vaccine period (decrease of 70.6%) compared to an increasing trend in the pre-vaccine period (SRR = 0.76, p = 0.02). In 25–34 year old men there was a significant decreasing trend in the vaccine period compared to no change in the pre-vaccine period (SRR = 0.81, p = 0.04) and in 35–44 year old men there was no significant change in rates of penile warts both periods, but the rate of change was greater in the vaccine period (SRR = 0.70, p = 0.02). CONCLUSIONS: The marked decline in in-patient treatment of vulval/vaginal warts in the youngest women is probably attributable to the HPV vaccine program. The moderate decline in in-patient treatments for penile warts in men probably reflects herd immunity.